Clostridium perfringens Periprosthetic Joint Infection: Case Report and Literature Review - Roman Dähler; Daniel Baunach; Roberto Buonomano (Annals of Internal Medicine: Clinical Cases)
Periprosthetic joint infection (PJI) remains a devastating complication after arthroplasty and very rarely PJI are due to anaerobes that usually lead to delayed and late infections. Here, we report on a patient with early-onset Clostridium perfringens PJI of the hip. The patient had a debridement with the exchange of removable components alongside a 12-week antibiotic treatment with penicillin and rifampicin, leading to a successful outcome. A thorough literature review of published case reports shows that Clostridium perfringens PJI either originate from intraoperative contamination or hematogenous spread. In most cases, the infection was successfully treated with surgical revision in combination with a prolonged course of antibiotics.